Designing of FAW and Striga agro-advisories and their delivery through a bulk SMS messaging to the farming communities in Rwanda - Senge, Moussa; Ouedraogo, Mathieu; Kagabo, Desire; Singh, Manjari; Landmann, Tobias (2023)
Rwanda is a predominantly agricultural country, and the agriculture sector employs over 70% of the population. The country's economy heavily relies on agriculture, which accounts for about 30% of the GDP. However, pests such as Fall Armyworm and Striga have posed a significant challenge to agricultural productivity in the country. These pests cause massive crop losses, and farmers have been struggling to manage them. Monitoring and early warning systems are key pieces for the strategic management of fall armyworm (FAW).